Amino acid profiles and clinical phenotypes in young children with autism spectrum disorder - Ilaria Serati; Luca Lalli; Andrea Riccardo Dallapiccola; Pietro Baso; Martina Tosi; Francesca Brustia; Maria Paola Canevini; Michele Mussap; Livia Pisciotta; Emilia Ricci; Maura Rossi; Marco Di Dario; et al. (Frontiers in Neuroscience, 2026)
Introduction In 394 children with autism spectrum disorder (ASD), we investigated the association between plasma amino acid (AA) concentrations and clinical phenotypes. Methods Multivariable logistic regression models were used to evaluate the associations between 22 AAs and clinical features, reporting odds ratios. Results The median age at diagnosis was 3.5 years (interquartile range: 2.8–4.6 years) for boys and 3.1 years (interquartile range: 2.3–3.8 years) for girls; 81.5% of the participants were boys. A 25-unit increase in cystine concentration was associated with stereotypies (OR = 2.07), hyperactivity (OR = 1.79), and aggressive behavior (OR = 2.13), suggesting a potential role of oxidative stress in these phenotypes. Similarly, a 25-unit increase in taurine levels was associated with hyperactivity (OR = 1.24) and intellectual disability (OR = 1.38), consistent with oxidative imbalance. Higher arginine levels appeared to have a protective effect against hyperactivity (OR = 0.70), indicating a potential role in ammonia detoxification. Increased glutamine and tyrosine levels were associated with ORs < 1 for stereotypies, supporting potential neuroprotective roles. Discussion These findings suggest oxidative stress, urea cycle dysfunction, and altered neurotransmission may contribute to the pathophysiology of ASD and related clinical phenotypes in young children, warranting further investigation to inform the development of personalized clinical and nutritional interventions.